The compound isolated from the leaves of Phyllostachys nigra protects oxidative stress-induced retinal ganglion cells death - Lee, Hee Ju; Kim, Kyung-A; Kang, Kui Dong; Lee, Eun Ha; Kim, Chul Young; Um, Byung Hun; Jung, Sang Hoon (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
This study was performed to determine whether the compound isolated from Phyllostachys nigra could attenuate oxidative stress in transformed retinal ganglion cells (RGC-5 cells) death. RGC-5 cells in culture were given two different insults such as 1-buthionine-(S,R)-sulfoximine (BSO) plus glutamate for 24 h or hydrogen peroxide for 24 h, after which cell survival were measured. Among the four systematic fractions tested, ethyl acetate fraction showed a significantly higher inhibition which was in a concentration dependent manner. Eight compounds were isolated from ethyl acetate fraction of P. nigra using preparative RP-HPLC and Sephadex LH-20 column chromatography. Their chemical structures were elucidated by chemical and spectral analysis as isoorientin (1), orientin (2), vitexin (3), cis-coumaric acid (4), p-coumaric acid (5), luteolin 6-C-(6 ''-O-trans-caffeoylglucoside) (6), vittariflavone (7) and tricin (8). The luteolin 6-C-(6 ''-O-trans-caffeoylglucoside) (compound 6) significantly attenuated the negative effects of BSO plus glutamate or hydrogen peroxide to RGC-5 cells. Treatment of the RGC-5 cells with compound 6 reduced the reactive oxygen species (ROS) as quantified using 2',7'-dichlorodihydrofluorescein diacetate (DCFH-DA). This compound also replenished the reduced glutathione level. In conclusion, these results implicate that compound 6 isolated from P. nigra could be used as a leading compounds for retinal disease via anti-oxidative effects. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: OPEN-ANGLE GLAUCOMA; OPTIC-NERVE HEAD; HYDROGEN-PEROXIDE; INDUCED APOPTOSIS; GLUTATHIONE; ANTIOXIDANT; HOMEOSTASIS; MECHANISMS; NEUROPATHY; REDUCTION